2020
DOI: 10.3390/nu12123797
|View full text |Cite
|
Sign up to set email alerts
|

Carbohydrate and Glutamine Supplementation Attenuates the Increase in Rating of Perceived Exertion during Intense Exercise in Hypoxia Similar to 4200 m

Abstract: The rating of perceived exertion (RPE) indicates the feeling of fatigue. However, hypoxia worsens the condition and can worsen RPE. We evaluated whether carbohydrate and glutamine supplementation alters RPE and physiological markers in running at 70% peak oxygen uptake until exhaustion in a simulated altitude of 4500 m. Nine volunteers underwent three running tests at 70% peak oxygen uptake until exhaustion: (1) hypoxia and placebo, (2) hypoxia and 8% maltodextrin, and (3) hypoxia after six days of glutamine s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 42 publications
1
2
0
1
Order By: Relevance
“…HR in all experimental tests increased linearly over the course of exercise. This replicates findings from our previous study [ 42 ] and from related adult work [ 43 , 44 ]. Although there were no significant differences, the pre-exercise and mixed tests had 5 bpm less HR means ± SD of cycles one to five than the placebo test.…”
Section: Discussionsupporting
confidence: 92%
“…HR in all experimental tests increased linearly over the course of exercise. This replicates findings from our previous study [ 42 ] and from related adult work [ 43 , 44 ]. Although there were no significant differences, the pre-exercise and mixed tests had 5 bpm less HR means ± SD of cycles one to five than the placebo test.…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, the reduction in symptoms of muscle damage due to glutamine supplementation may be attributed to various factors including increased availability of amino acids, additional energy intake from supplementation, and elevated protein synthesis. Moreover, Caris and Thomatieli-Santos (2020) suggested that glutamine intake (20 g/d for six days) prior to intense exercise may reduce the increase in RPE and could be a beneficial strategy for those engaged in exercise. Similarly, in a study assessing resistance-trained male athletes, Paiva et al (2020) administered creatine supplementation (20 g/d) for seven days.…”
Section: Discussionmentioning
confidence: 99%
“…Acute or chronic glutamine supplementations have been widely applied to take advantage of its antioxidant, anti-inflammatory, and immuno-regulating capacity. Recently, Caris and colleagues reported that 6-day glutamine (20 g/day) supplementation enhances in-trial glycemia and attenuates the increase in RPE ( n = 9, treadmill exercise to exhaustion, 70% VO 2max ) [ 34 ]. Cystine is an oxidized form of cysteine.…”
Section: Discussionmentioning
confidence: 99%